2020
DOI: 10.1016/j.obmed.2020.100302
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome dysbiosis and endotoxemia - Additional pathophysiological explanation for increased COVID-19 severity in obesity

Abstract: The overall intestinal lipopolysaccharide (LPS) composition in the individuals with obesity could be shifted away from immunosilent/immunoinhibitory Bacteroidetes LPS subtypes, in favor of various proinflammatory LPS subtypes due to gut microbiome dysbiosis. What is more, high-fat diet, as well as obesity per se, enhance intestinal permeability through various mechanisms. Latter results in increased paracellular absorption and transcellular (via chylomicrons) transport of endogenous endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 15 publications
2
62
0
1
Order By: Relevance
“…Accumulating body of literature is generally consistent that individuals with diabetes mellitus type 2 and/or obesity have altered intestinal microbiota which is characterized by significantly higher level of Firmicutes and lower level of Bacteroidetes (decreased B/F ratio), compared to healthy/normal‐weight individuals 57‐63 . Hence, the intestinal LPS in the individuals with diabetes mellitus type 2 and/or obesity could be shifted away from immunosilent/immunoinhibitory Bacteroidetes LPS subtypes, in favour of various proinflammatory LPS subtypes (phyla producing more inflammatory LPS) 52,56 . As recently extensively described, latter shift accompanied by enhanced intestinal permeability may then result in endotoxemia and activation of proinflammatory pathways (predominantly NF‐ĸB) 52 .…”
Section: Glp‐1ras and The Effect On Gut Microbiome Compositionmentioning
confidence: 96%
See 1 more Smart Citation
“…Accumulating body of literature is generally consistent that individuals with diabetes mellitus type 2 and/or obesity have altered intestinal microbiota which is characterized by significantly higher level of Firmicutes and lower level of Bacteroidetes (decreased B/F ratio), compared to healthy/normal‐weight individuals 57‐63 . Hence, the intestinal LPS in the individuals with diabetes mellitus type 2 and/or obesity could be shifted away from immunosilent/immunoinhibitory Bacteroidetes LPS subtypes, in favour of various proinflammatory LPS subtypes (phyla producing more inflammatory LPS) 52,56 . As recently extensively described, latter shift accompanied by enhanced intestinal permeability may then result in endotoxemia and activation of proinflammatory pathways (predominantly NF‐ĸB) 52 .…”
Section: Glp‐1ras and The Effect On Gut Microbiome Compositionmentioning
confidence: 96%
“…hypertension, dyslipidemia, diabetes), as an adjunct to diet and exercise 42‐45,50 . Anti‐obesogenic properties of long‐acting GLP‐1RAs are even more desirable now during the times of COVID‐19 pandemic, since obesity is associated with increased COVID‐19 susceptibility and severity due to low‐grade chronic inflammation, higher expression of ACE‐2 and pathway associated components, as well as decreased vitamin D bioavailability and gut microbiome dysbiosis 51,52 . To clarify, a decrease in BMI and fat mass due to GLP‐1RA usage has a beneficial effect on previously mentioned components, which finally results in reduction of overall COVID‐19 susceptibility and risk for development of its more severe clinical forms.…”
Section: Glp‐1ras and Anti‐obesogenic Propertiesmentioning
confidence: 99%
“…Moreover, the small intestine expression of ACE2 receptors and respiratory virus infection is associated with dysbiosis of the gut microbiota [ 76 ] ( Figure 1 ). Dysbiosis and endotoxemia have been implied in the observed increase of COVID-19 severity in obesity [ 77 ]. Metabolic endotoxemia could be induced by the direct diffusion of the Gram negative endotoxin lipopolysaccharide (LPS) from the intestinal lumen, due to intestinal paracellular permeability resulting from dysbiosis [ 78 , 79 ], or through the absorption by enterocytes during the secretion of chylomicrons in the postprandial state [ 80 ].…”
Section: Diabesity Meta-inflammation and Il-6: The Role In Severmentioning
confidence: 99%
“…Unexpectedly, a previous investigation showed that in type 1 diabetes rats, GLP-1 receptor (GLP-1R) activation by Liraglutide increased ACE2 expression, which reversed the right ventricle hypertrophy in the heart, and improved the production of surfactant proteins (SP-A and SP-B) in the lungs ( 39 ). A follow-up study showed that Liraglutide prevented the alteration in lung function induced by in utero growth retardation (IUGR) and promoted the positive effects of ACE2-Ang ( 1 , 2 , 3 , 4 , 5 , 6 , 7 ) system in restoring lung function ( 40 ).…”
Section: Diabetic Medicine: Glucagon-like Peptide-1 (Glp-1)mentioning
confidence: 99%
“…A recent study indicates that the diabetes drug metformin is able to reduce the mortality rate in the COVID-19 patients ( 3 ). Intensive investigations have been conducted in exploring the relationship between obesity and the severity of COVID-19 ( 4 , 5 , 6 ). Here we would like to present a commentary on the use of the two categories of therapeutic agents in COVID-19 patients with metabolic disorders including obesity, T2D and CVD.…”
Section: Introductionmentioning
confidence: 99%